The effect of reducing welfare access on employment, health, and children's long-run outcomes - Jeffrey Hicks; Gaëlle Simard-Duplain; David A. Green; William Warburton (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
Welfare caseloads in North America halved following reforms in the 1990s and 2000s. We study how this shift affected families by linking Canadian welfare records to tax returns, medical spending, educational attainment, and crime data. We find substantial and heterogeneous employment responses that increased average income despite reduced transfers. We find zero effects on aggregate health expenditures, but mothers saw reduced preventative care and increased mental health treatment, consistent with the transition to employment elevating time pressure and stress. We find no effect on teenagers' education and criminal charges as young adults but do find evidence of intergenerational welfare transmission.
Keywords: H23; H31; I14; I24; I38; J62; 330